Ministry of the Mushroom. (23rd March 2022) - Lutkajtis, Anna
Abstract : Recently there has been a surge of renewed interest in the psychedelic compound psilocybin. In particular, psilocybin is being studied in clinical settings as a potential breakthrough treatment for depression. Alongside this growing therapeutic interest, there has been a rise in the religious use of psilocybin, as evidenced by the creation of a number of psilocybin mushroom churches in the United States. While the dominant popular discourse surrounding psilocybin is currently clinical, psilocybin churches offer an alternative form of meaning making regarding the psychedelic experience. Specifically, this article argues that psilocybin churches enable their followers to participate in a dynamic social process of "sacred sensemaking, " whereby psilocybin mushrooms are considered to be a sacrament, church members follow a ritual-based psychopharmacological practice, and the psychedelic experience is interpreted in terms of a direct encounter with the divine. Different psilocybin churches have unique approaches, ritual practices and cosmologies, nonetheless this article suggests that they may be united by this common process of sacred sensemaking.